2014
DOI: 10.1111/evj.12378
|View full text |Cite
|
Sign up to set email alerts
|

Foot placement of the equine forelimb: Relationship between foot conformation, foot placement and movement asymmetry

Abstract: A relationship exists between foot conformation and movement asymmetry with decreasing hoof width and hoof length related to increasing amount of movement asymmetry. In the population of horses studied here--deemed to be 'well functioning' by their owners/riders--foot placement was found to be independent of movement asymmetry and, to a large extent, independent of foot conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…Dorsopalmar and lateromedial foot placement did not vary significantly across the three surfaces at walk or trot so Hypothesis 2 is not supported. ‘Mixed’ dorsopalmar and lateromedial foot‐placement classifications were most common at trot which is in agreement with previous work . However, at walk our results differ from previous work as we reported ‘flat’ as the most common classification whereas others reported ‘mixed’ .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Dorsopalmar and lateromedial foot placement did not vary significantly across the three surfaces at walk or trot so Hypothesis 2 is not supported. ‘Mixed’ dorsopalmar and lateromedial foot‐placement classifications were most common at trot which is in agreement with previous work . However, at walk our results differ from previous work as we reported ‘flat’ as the most common classification whereas others reported ‘mixed’ .…”
Section: Discussionsupporting
confidence: 84%
“…lateral heel. While it is generally accepted that a well‐balanced foot should land flat, to evenly distribute limb force , previous work suggests that, at trot, lateral foot placement is most common in the forelimbs and that horses show inconsistencies in foot‐placement, which is not influenced by foot confirmation or lameness .…”
Section: Introductionmentioning
confidence: 99%
“…Also, our IMU approach demonstrated a better overall accuracy in detecting the hoof‐off moment. We suggest that this can be explained by the fact that the motion capture detection algorithm is more affected by hoof conformation and variation in foot placement 22, since the algorithm depends on how the toe/heel are elevated from the ground and this can be affected by hoof conformation, whereas the IMU measures the actual limb movement resulting from the hoof‐off event. Recent research reported that there was a high degree of variation in foot placement in horses 22, 23 and this is thus more likely to affect our described motion capture algorithm than the IMU method.…”
Section: Discussionmentioning
confidence: 99%
“…Guidance in achieving mediolateral balance of the equine foot refers to the trimming of the medial and lateral walls, to ensure that the live sole of the foot is level with the ground [35] and the hoof is in balance with the limb column [27], as opposed to the postulation that balance is attained through the attainment of symmetrical wall lengths [29]. More recent studies have found that subtle asymmetries manifested as a more upright medial wall and a more angled lateral wall are common within the domestic horse population [8,36,37,38,39] and reflect the lateral landing and unrollment pattern of the foot observed in sound horses [17,40]. Our results support the practice of trimming according to the live sole, with a more inclined conformation, without altering the mediolateral balance of the foot, to promote soundness and not change the wall lengths.…”
Section: Discussionmentioning
confidence: 99%